Increased DNA methylation in the spermatogenesis‐associated (SPATA) genes correlates with infertility. (2nd January 2020) - Sujit, Kumar Mohanty; Singh, Vertika; Trivedi, Sameer; Singh, Kiran; Gupta, Gopal; Rajender, Singh
Abstract: Background: Spermatogenesis‐associated (SPATA) family of genes plays important roles in spermatogenesis, sperm maturation or fertilization. The knockout studies in mice have demonstrated that SPATA genes are crucial for fertility. Gene expression and genetic polymorphism studies have further suggested their correlation with infertility; however, methylation analysis of SPATA genes in human male infertility has not yet been undertaken. Objectives: To analyze the methylation status of SPATA4, SPATA5 and SPATA6 genes in oligozoospermic male infertility. Materials and methods: In the present study, we have analyzed DNA methylation pattern in the promoter regions of SPATA4, SPATA5 and SPATA6 genes in oligozoospermic patients and compared it with normozoospermic fertile controls. Semen samples were obtained from 30 oligozoospermic infertile and 19 normozoospermic fertile controls, and DNA methylation levels of the target gene promoters were analyzed by amplicon based deep sequencing methylation analysis using MiSeq. Results: SPATA4 ( P  < 0.0008), SPATA5 ( P  = 0.009) and SPATA6 (Promoter, P  < 0.0005; Exon 1, P  = 0.0128) genes were significantly hypermethylated in oligozoospermic patients in comparison to controls. This is the first study reporting a higher methylation in the promoters of SPATA4, SPATA5 and SPATA6 in oligozoospermic infertile individuals in comparison to the normozoospermic fertile controls. Discussion: Altered methylation of SPATA genes would affect pathways involved in sperm production or affect various processes linked to sperm fertility. Conclusion: In conclusion, hypermethylation in the SPATA4, SPATA5 and SPATA6 genes correlates with oligozoospermic infertility.